The burning of Rosemont Abbey - Stephens, Naomi (Bethany House Publishers, a division of Baker Publishing Group, 2024)
"In the sleepy post-war English village of Wilbeth Green, everyone believes Paul Everly burned Rosemont Abbey, then disappeared. Only his twin sister, Louisa, is certain of his innocence. With the aid of Inspector Malcolm Sinclair, Louisa will stop at nothing to clear her brother's name and solve a murder no one else believes was committed"--